Enabling public, patient and practitioner involvement in co-designing frailty pathways in the acute care setting - Deirdre O'Donnell; Éidín Ní Shé; Mary McCarthy; Shirley Thornton; Thelma Doran; Freda Smith; Barry O'Brien; Jim Milton; Bibiana Savin; Anne Donnellan; Eugene Callan; Eilish McAuliffe; et al. (BMC, 2019)
Abstract Background Although not an inevitable part of ageing, frailty is an increasingly common condition in older people. Frail older patients are particularly vulnerable to the adverse effects of hospitalisation, including deconditioning, immobility and loss of independence (Chong et al, J Am Med Dir Assoc 18:638.e7-638.e11, 2017). The 'Systematic Approach to improving care for Frail older patients' (SAFE) study co-designed, with public and patient representatives, quality improvement initiatives aimed at enhancing the delivery of care to frail older patients within an acute hospital setting. This paper describes quality improvement initiatives which resulted from a co-design process aiming to improve service delivery in the acute setting for frail older people. These improvement initiatives were aligned to five priority areas identified by patients and public representatives. Methods The co-design work was supported by four pillars of effective and meaningful public and patient representative (PPR) involvement in health research (Bombard et al, Implement Sci 13:98, 2018; Black et al, J Health Serv Res Policy 23:158-67, 2018). These pillars were: research environment and receptive contexts; expectations and role clarity; support for participation and inclusive representation and; commitment to the value of co-learning involving institutional leadership. Results Five priority areas were identified by the co-design team for targeted quality improvement initiatives: Collaboration along the integrated care continuum; continence care; improved mobility; access to food and hydration and improved patient information. These priority areas and the responding quality improvement initiatives are discussed in relation to patient-centred outcomes for enhanced care delivery for frail older people in an acute hospital setting. Conclusions The co-design approach to quality improvement places patient-centred outcomes such as dignity, identity, respectful communication as well as independence as key drivers for implementation. Enhanced inter-personal communication was consistently emphasised by the co-design team and much of the quality improvement initiatives target more effective, respectful and clear communication between healthcare personnel and patients. Measurement and evaluation of these patient-centred outcomes, while challenging, should be prioritised in the implementation of quality improvement initiatives. Adequate resourcing and administrative commitment pose the greatest challenges to the sustainability of the interventions developed along the SAFE pathways. The inclusion of organisational leadership in the co-design and implementation teams is a critical factor in the success of interventions targeting service delivery and quality improvement.